ECHOES AND REFLEXES OF PENTECOSTALISM IN THE CLASSES OF PHYSICAL EDUCATION AND FOLKLORE (Fiep Bulletin - online, 2014)
The objective of this work is to analyze the relationships and interferences of the regiment of the church "Deus é Amor" in the classes of Physical Education when contents of the Afro-Brazilian folklore are developed. The focus is in the analysis of the internal regiment of the religious institution in relation to the corporal practices, being observed the ones that are anchored in the imaginary Afro-Brazilian. We verified that the regiment of that church tends to hinder the participation of its members in cultural activities that involve sound rhythms produced by batteries and pandeiros. Besides, the practices of the soccer, other element of the national culture, are forbidden for the regiment. The subject is ethical. Does tend in view the growth of the cultural structures of information and communication in detriment of the social structures, as to preserve the partner-cultural patrimony without confronting it with the new cultural structures what they come more and more strong? Could the popular culture serve to the " resistance " and not to the dominance? How to develop contents of the popular culture in the classes of physical education in way to question the dominance structures exercised by new cultural structures of religion?
Keywords: physical education; religion; racism